Effect of Smoking on Lung Function Decline in a Retrospective Study of a Health Examination Population in Chinese Males - Tian, Ting; Jiang, Xueqin; Qin, Rujie; Ding, Yuqing; Yu, Chengxiao; Xu, Xin; Song, Ci (Frontiers in Medicine, 2023)
Objective: China has established a goal of reducing adult smoking prevalence from 27.7% to 20% by 2030. Understanding the possible ongoing impairment in lung function in smokers, is critically important to encourage the populations to change their smoking behavior. Methods: A total of 14,273 males joined the health examination at Huadong Sanatorium from Jan 2012 to Dec 2019 were included. In cross-sectional analysis, we used multiple linear regression to evaluate the association between baseline lung function and smoking status. Then, 3,558 males who received ≥2 spirometry exams were analyzed in longitudinal study. Annual lung function decline was compared using mixed linear models adjusted for confounders. Results: In cross-sectional analysis, compared with never-smokers, decreases of -133.56 mL (95% CI: -167.27, -99.85) and -51.44 mL (-69.62, -33.26) in FEV1, -1.48% (-1.94, -1.02) and -1.29% (-1.53, -1.04) in FEV1/FVC were observed in former and current smokers. In longitudinal analysis, significant declines were observed in FEV1 (5.04 (2.30, 7.78) mL) and FEV1/FVC (0.09 (0.05, 0.13) %) in current smokers but not observed in former smokers after adjustment. Participants with long duration of smoking cessation had decelerate lung function than short duration. The annual decline rate of current smokers with high smoking intensity (≥30 cigarettes per day) was 13.80 and 14.17 times greater than that of never-smokers in FEV1 and FVC. Thus, early smoking cessation can slow down lung function decline trend for current smokers. Conclusions: The harms of current smoking on lung function emphasize the necessity of smoking cessation, especially for those with comorbidities.